Longitudinal Solid Polarized Target for CLAS12 - Pandey, P.; Kuhn, S.; Lagerquist, V.; Keith, C.; Brock, J.; Maxwell, J. (Journal of Nepal Physical Society, 2022)
The Run Group C suite of experiments measure multiple spin-dependent observables by scattering an 11 GeV electron beam from longitudinally polarized nucleon targets inside the CLAS12 spectrometer in Hall B at Jefferson Lab. The dynamically polarized target built for these experiments has been extensively tested by the JLab Target Group in the Experimental Equipment Lab using an auxiliary 5 T magnet. We report on the operational experience with the target, the benchmarks achieved so far (using various polarizable materials) as well as the complete target setup, experimental readiness, and its present status. Our results show that all target components work well and the project has started successfully with the first beam on June 11, 2022.